2017
DOI: 10.1186/s41118-017-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional poverty, household environment and short-term morbidity in India

Abstract: Using the unit data from the second round of the Indian Human Development Survey (IHDS-II), 2011–2012, which covered 42,152 households, this paper examines the association between multidimensional poverty, household environmental deprivation and short-term morbidities (fever, cough and diarrhoea) in India. Poverty is measured in a multidimensional framework that includes the dimensions of education, health and income, while household environmental deprivation is defined as lack of access to improved sanitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Multiple conditions have been linked to social and environmental determinants of health (SEDOH). 10 , 11 , 12 The 2020 Lancet Commission on dementia prevention, intervention, and care identified twelve potentially modifiable risk factors that have been documented to date, including smoking, air pollution, hypertension, depression, traumatic brain injury, absence of education, and social exclusion. 13 The World Health Organization recently acknowledged that inequalities in SEDOH during the life course such as access to care, treatments, and healthy diets may increase the risk of cognitive impairment and dementia prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple conditions have been linked to social and environmental determinants of health (SEDOH). 10 , 11 , 12 The 2020 Lancet Commission on dementia prevention, intervention, and care identified twelve potentially modifiable risk factors that have been documented to date, including smoking, air pollution, hypertension, depression, traumatic brain injury, absence of education, and social exclusion. 13 The World Health Organization recently acknowledged that inequalities in SEDOH during the life course such as access to care, treatments, and healthy diets may increase the risk of cognitive impairment and dementia prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The global MPI report 2018 shows that India is home to the largest number of multidimensionally poor people (364 million), but their spatial distribution is skewed (inequality among the poor is 0.014). In the Indian context, Bhuiya et al (2007) found health, education, housing and clothing as significant contributors to multidimensional poverty; Alkire and Seth (2015) found housing, electricity, safe drinking water and sanitation as significant determinants of multidimensional poverty; Bhat (2013) found health, education, housing, sanitation and electricity as the significant determinants of multidimensional poverty in Jammu and Kashmir (J&K); Mishra and Shukla (2015) observed that rural multidimensional poverty predominates J&K; Dehury and Mohanty (2017) found health, sanitation, drinking water and cooking fuel as the significant contributors to multidimensional poverty; Mohanty et al (2017) observed that health shocks to households are the main reasons behind multidimensional poverty; Banerjee et al (2017) state that the major reason behind the concentration of multidimensional poverty in rural India is urban-biased policies of the government. In a district-level study, Mehta (2003) identified illiteracy, infant mortality, low levels of agricultural productivity and poor infrastructure as the primary causes of persistent deprivation leading to multidimensional poverty at the district level in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a village-level study, Unjum and Mishra (2018) observed that the deprivations in the form of low level of schooling, malnutrition, use of traditional fuel for cooking, bad sanitation facilities and informal employment mainly contribute to multidimensional poverty in Kashmir. Therefore, the incidence and intensity of multidimensional poverty can be reduced by improving the level of education (Berenger & Verdier-Chouchane, 2007), housing and income-generating employment standards (Bibi, 2004), and also by improving the level of nutritional intakes, safe drinking water supply, sanitation, hygiene and cooking fuel (Alkire & Seth, 2015; Dehury & Mohanty, 2017; Giné-Garriga & Pérez-Foguet, 2018; Unjum & Mishra, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“… 10 It is well documented that poor social determinants of health are directly associated with disease. 11 , 12 , 13 , 14 , 15 , 16 However, to our knowledge, limited research exists investigating how social determinants of health are associated with dementia. Context-specific studies using multidimensional poverty measures are required to better understand this association.…”
Section: Introductionmentioning
confidence: 99%
“…The 2020 Lancet Commission on dementia prevention, intervention, and care identified 12 potentially modifiable risk factors for dementia, including poor education, hypertension, depression, low social contact, smoking, air pollution, and traumatic brain injury . It is well documented that poor social determinants of health are directly associated with disease . However, to our knowledge, limited research exists investigating how social determinants of health are associated with dementia.…”
Section: Introductionmentioning
confidence: 99%